Modeling of mycelial growth of parental, hybrid and reconstituted strains of Pleurotus and Lentinula - Valenzuela-Cobos, J. D.; Rodríguez-Grimón, R. O.; Jara-Bastidas, M. L.; Grijalva-Endara, A.; Zied, D. C. [UNESP]; Garín-Aguilar, M. E.; del Toro, G. Valencia (Universidad Autonoma Metropolitana, 2020)
The kinetics of mycelial growth of parental strains, hybrid and reconstituted of Pleurotus and Lentinula was calculated using the mycelial growth diameter for (malt extract agar) MEA and for wheat grain was determinate using the mycelial growth volume, the parameters were adjusted to 3 nonlinear models (Baranyi, Exponential, Logistic) and one Linear Model to determine the specific growth speed (μmax) and lag phase time (λ). The hybrid and reconstituted strains of Pleurotus spp. and Lentinula showed similar mycelial morphology with exception of the hybrid PD4xLC3. The mycelial kinetics of the dikaryotic strains on MEA using 4 mathematical models showed a μmaxbetween 6.30 and 23.49 mm day-1 and the lag phase ranged from 0.22 to 4.47 h; while on wheat grain presented μmax since 0.08 to 11.41 cm3 day-1 and lag duration between 0.06 and 8.04 h. The hybrid strain PO5xLC2 and the reconstituted strain of Pleurotus djamor PD1xPD4 showed the highest μmax and lowest lag phase on MEA and wheat grain respectively in comparison to the other strains include their parental strains. The results evidenced that the use of hybrid and reconstitued strains of Pleurotus and Lentinula presented highest mycelial growth kinetics on EMA and on wheat grain in relation to their parental strains.
Modelamiento de crecimiento micelial de cepas parentales, híbridas y reconstituidas de pleurotus y lentinula
Keywords: Hybrid; Morphology; Mycelial growth; Reconstituted strains